Weaknesses of contemporary management methods in the opinion of polish managers-practitioners - Kaczmarek, B. (Економічний вісник Донбасу, 2018)
The article presents two issues: a short description of the most important (according to the author) 16 contemporary management methods and the presentation of the opinion of the group of 18 top managers of medium and large enterprises from the Lodz region, nominated by local governments to the Lodz Voivodship Economic Award in the year 2017 on the “knowledge and practical use of modern management methods”. The opinions of the managerial staff surveyed in the report are based on pilot studies, on the basis of which the above-mentioned opinions cannot be generalized or disseminated, but it is worth to read them, because these are the opinions of the Governors (Best Managers) in the Lodzier Voivodship – in relation to economic and financial results achieved in the last three years – enterprises.